Atomic orbitals and their representation: can 3-D computer graphics help conceptual understanding? - Trindade,Jorge (2005)
Quantum mechanics is a non-intuitive subject. For example, the concept of orbital seems too difficult to be mastered by students who are starting to study it. Various investigations have been done on student's difficulties in understanding basic quantum mechanics. Nevertheless, there are few attempts at probing how student's understanding is influenced by appropriate visualization techniques, which are known to help conceptual understanding. ''Virtual Water'' is a 3-D virtual environment we have designed and built to support the learning of Physics and Chemistry at final high school and first-year university levels. It focuses on the microscopic structure of water and explores, among others, atomic and molecular orbitals. Having asked a group of first-year students of Sciences and Engineering courses at the University of Coimbra, Portugal, to describe how they conceive electrons in atoms we found some common misconceptions. We have tried, with partial success, to overcome them by making students explore our virtual environment. The most relevant characteristics of the virtual environment which contributed to student's conceptual understanding were 3-D perception and navigation.